THE ORIGINALITY OF THE STORY “THE LIFE OF GENGHIS KHAN BY V.I.DALYA - U. Jurakulov; M. Bayeshanov (Galaxy International Interdisciplinary Research Journal, 2023)
The content of V, I Dahl’s work "The Life of Genghis Khan " echoes the Bible, the Koran, and "Kissai Rabguzi" ("Rabguzi’s Stories about the prophets") Nasruddin Burhanuddin Rabguzi was a Turkic poet who lived in Khorezm in the 13th century.